2016
DOI: 10.1093/conphys/cow058
|View full text |Cite
|
Sign up to set email alerts
|

Parasites, stress and reindeer: infection with abomasal nematodes is not associated with elevated glucocorticoid levels in hair or faeces

Abstract: We used captive reindeer to determine whether Ostertagia gruehneri, a common gastrointestinal nematode of Rangifer, caused increased stress as measured by hair and faecal glucocorticoids. We found that reindeer infected with an ‘average’ dose of this parasite did not have higher stress levels compared with uninfected control animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 85 publications
(124 reference statements)
3
25
0
Order By: Relevance
“…However, the peak FCM levels were lower when compared to the ACTH challenge test. A study by Carlsson et al [26] found no increase in FCM levels eight hours after handling stress, but their method was not validated for this species. This underlines the importance of performing validation studies in every animal species and validating each method of FCM analysis against baseline values found under practical and representative conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the peak FCM levels were lower when compared to the ACTH challenge test. A study by Carlsson et al [26] found no increase in FCM levels eight hours after handling stress, but their method was not validated for this species. This underlines the importance of performing validation studies in every animal species and validating each method of FCM analysis against baseline values found under practical and representative conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lower probability of survival was associated with higher hair cortisol in grey mouse lemurs ( Microcebus murinus; Rakotoniaina et al., ) as well as higher hair corticosterone in root voles ( Microtus oeconomus ; Książek et al, ). Other studies have used hair cortisol to investigate the effects of social status (Koren & Geffen, ; Koren et al., ), social density (Dettmer, Novak, Meyer, & Suomi, ; Grigg, Nibblett, Robinson, & Smits, ; Salas et al., ), human disturbance (Agnew, Smith, & Fowkes, ; Bourbonnais, Nelson, Cattet, Darimont, & Stenhouse, ; Ewacha, Roth, Anderson, Brannen, & Dupont, ; Fourie et al., ; Lyons, Mastromonaco, Edwards, & Schulte‐Hostedde, ), hunting (Bryan et al., ), diet (Bryan, Darimont, et al, ; Lafferty, Laudenslager, Mowat, Heard, & Belant, ), resource availability (Bryan et al., ), parasitism (Carlsson, Mastromonaco, Vandervalk, & Kutz, ), season (Di Francesco et al., ), and climate variability (Bechshøft et al., ; Fardi, Sauther, Cuozzo, Jacky, & Bernstein, ; Macbeth, Cattet, Obbard, Middel, & Janz, ).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have used hair cortisol to investigate the effects of social status (Koren & Geffen, 2009;Koren et al, 2006), social density (Dettmer, Novak, Meyer, & Suomi, 2014;Grigg, Nibblett, Robinson, & Smits, 2017;Salas et al, 2016), human disturbance (Agnew, Smith, & Fowkes, 2016;Bourbonnais, Nelson, Cattet, Darimont, & Stenhouse, 2013;Ewacha, Roth, Anderson, Brannen, & Dupont, 2017;Fourie et al, 2015;Lyons, Mastromonaco, Edwards, & Schulte-Hostedde, 2017), hunting (Bryan et al, 2015), diet (Bryan, Darimont, et al, 2013;Lafferty, Laudenslager, Mowat, Heard, & Belant, 2015), resource availability (Bryan et al, 2014), parasitism (Carlsson, Mastromonaco, Vandervalk, & Kutz, 2016), season (Di Francesco et al, 2017), and climate variability (Bechshøft et al, 2013;Fardi, Sauther F I G U R E 1 Procedure for analysis of steroid hormones in hair from wild and domestic animals. Typical steps include (1) initial hair prep (e.g., removal of follicles, sorting guard hairs from underfur), (2) washing (e.g., 1-3× with water and 1-3× with isopropanol), (3) cutting or grinding (optional), (4) weighing hair into a vial, (5) extraction of steroids from hair using a solvent (typically methanol), (6) separation of extract from hair matrix by centrifugation, and (7) analysis using EIA, RIA, or LC-MS/MS.…”
Section: Biological Validations and Applicationsmentioning
confidence: 99%
“…Environmental factors that affect cortisol levels and body condition of ungulates include parasites, disease, reproductive output, disturbance, habitat quality, weather, climate, starvation and/or injury. Body condition can be negatively related to parasite infection, although the effect size is variable (Carlsson et al , 2016; Sánchez et al , 2018). We did not examine the effect of parasites on body condition on ungulates in our study area, although there was an outbreak of anthrax due to Bacillus anthracis that killed 28 bison in our study area in 2008 (Shury et al , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…capture and restraint), which can initiate the stress response and alter GC levels (Kersey and Dehnhard, 2014). Minimally invasive methods of GC quantification often use feces, urine, feathers and hair as alternatives (Lafferty et al , 2015; Carlsson et al , 2016; Dantzer et al , 2016; Di Francesco et al , 2017; Seeber et al , 2018). Quantification of fecal GCs has been conducted on a wide range of taxa and provides a measure of stress during the time of gut passage (Bonier et al , 2004; Schwarzenberger, 2007; Kersey and Dehnhard, 2014; Rolland et al , 2017).…”
Section: Introductionmentioning
confidence: 99%